Mediumistic Phenomena by Julian Ochorowicz Part II - Weaver, Zofia (Journal of Scientific Exploration, 2018)
Translated by Casimir Bernard and Zofia Weaver, edited by Zofia Weaver Part I appeared in JSE 32:1, Spring 2018, and included the sections: Introduction, Excursion in Search of New Truths, A New Category of Phenomena. Part II published here includes the sections: Warsaw Experiments with Eusapia Palladino, Official Sittings, and Conclusions Drawn from the Warsaw Experiments. DOI: https://doi.org/10.31275/2018.1277B Preface Summary—Having returned from Rome a mediumist, Ochorowicz devoted all summer to studying the literature on mediumship and was amazed at how quickly it could be done—with a few significant works and hundreds of books of greater or lesser interest but no scientific value. That made him appreciate all the more the work of Crookes, Zollner, Du Prel, and Gibier. However, Crookes offers no theory and his observations stand alone as a register of facts that are hard to believe; this is a problem that can be rectified by reference to hypnotism, something achieved by Aksakov (who is a spiritist and accepts many sources which seem very dubious to Ochorowicz). P.S. The Preface, and the account of Warsaw Experiments with Eusapia Paladino which follows, were written in 1894, but the hostile attitude of the public in Poland to the question of mediumship meant that the report spent 19 years in Ochorowicz’s desk. —Zofia Weaver